Analysis of Federal Transfer Policy in Russia - Sumskaya, T. V. (Studies on Russian economic development, 2024)
— The budget revenues of the federal subjects of the Russian Federation for the period 2012–2020 at constant prices are analyzed. The territories with maximum and minimum amounts of tax and nontax revenues, as well as gratuitous transfers, have been identified. To determine the direction of the federal center’s budget policy, indicators of heterogeneity of tax and nontax revenues, total revenue and gratuitous transfers received by regional budgets, and Spearman’s rank correlation coefficient for regional revenues with and without accounting for these transfers were calculated. Using regression analysis tools, it was established that, in general, budget policy is aimed at smoothing out interregional differences in the structure of budget revenues of Russian regions; however, regions need broader tax powers, which will increase their interest in increasing tax revenues. The composition of the regions with the lowest values of tax and nontax revenues practically did not change during the period under review; thus, it is impossible to draw a conclusion about the effectiveness of the applied transfer mechanism.